Day‐by‐day variation in affect, arousal and alcohol consumption in young adults. (15th January 2015) - Peacock, Amy; Cash, Catherine; Bruno, Raimondo; Ferguson, Stuart G.
Abstract Introduction and Aims Alcohol consumption has a well‐established relationship with mood, with higher positive and negative affect predicting alcohol use. More recently, researchers have explored whether alcohol consumption occurs as a response to affect variability as an attempt to self‐medicate and stabilise affect. Studies have revealed a positive association between alcohol use and intra‐ and inter‐individual affect variability in clinical and university student samples; however not much is known of this relationship among the general community. Design and Methods Ecological Momentary Assessment (EMA) methods were used to investigate the relationship between affect and arousal variability and alcohol use in 53 community volunteers. Participants self‐reported affect and arousal at three to five randomly timed moments throughout the day, as well as every time they drank. Results On a day‐to‐day basis, higher positive affect was associated with increased alcohol consumption. When analyses were restricted to self‐reported affect prior to alcohol consumption, only increased arousal and decreased variability in arousal predicted the likelihood of alcohol consumption. Mean level of arousal was associated with the extent of alcohol consumed. Discussion and Conclusions In this moderate drinking sample day‐to‐day affect and arousal, and arousal variability, were associated with alcohol consumption. Analyses restricted to pre‐drinking observations provide further evidence that self‐medication accounts of alcohol consumption may explain drinking initiation but that the relationship between affect factors and drinking behaviour may change around the point of first drink. [Peacock A, Cash C, Bruno R, Ferguson SG. Day‐by‐day variation in affect, arousal and alcohol consumption in young adults. Drug Alcohol Rev 2015;34:588–94]